THE MAKING OF DIGITAL TEACHING MATERIALS FOR FINANCIAL ACCOUNTING SUBJECT FOR CLASS XII SEMESTER 1 AT SMK NEGERI 1 TANJUNGPINANG - Sukiantono Tang; Natalia Harini (ConCEPt - Conference on Community Engagement Project, 2022)
The spread of the Covid-19 pandemic that occurred in early 2020 caused the education sector to carry out its online teaching and learning process. This indirectly creates a challenge for SMK Negeri 1 Tanjungpinang which results in SMK Negeri 1 Tanjungpinang being unable to deliver materials effectively to their students due to space and time limitations in the process of designing teaching materials so that digital teaching materials are made to support the learning process at SMK Negeri 1 Tanjungpinang. The preparation of the material is obtained from financial accounting e-books and website references. The teaching materials made are in the form of modules, powerpoints, and learning videos based on Core Competencies and Basic Competencies (KIKD). The teaching materials that will be implemented in the coming semester are expected to help teachers and students at SMK Negeri 1 Tanjungpinang increase their effectiveness and efficiency in carrying out the online teaching and learning process. The recommendation for the next project is to be more variated by adding animated videos with more relavant information that still within the scope.